2023
DOI: 10.1088/1361-6560/acfec5
|View full text |Cite
|
Sign up to set email alerts
|

The first investigation of spot-scanning proton arc (SPArc) delivery time and accuracy with different delivery tolerance window settings

Gang Liu,
Lewei Zhao,
Peilin Liu
et al.

Abstract: Objective: To investigate the impact of various delivery tolerance window settings on the treatment delivery time and dosimetric accuracy of spot-scanning proton arc (SPArc) therapy.
Approach: SPArc plans were generated for three representative disease sites (brain, head neck, and liver cancer) with an angle sampling frequency of 2.5 degrees. An in-house dynamic arc controller was used to simulate the arc treatment delivery with various tolerance windows (±0.25, ±0.5, ±1, and ±1.25 degrees). The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has, however, been shown that, while PAT delivery times exceed IMPT treatment times when energy layer switching times are higher, delivery times of proton arc therapy treatments can become equivalent to or even lower than their IMPT counterparts if energy layer switching is sufficiently fast (Ding et al 2016, Liu et al 2020b, 2023a). An increase in the delivery tolerance window up to ±1.25°has been to be capable of considerably reducing PAT delivery times as well (Liu et al 2023b). The extent to which delivery times of IMPT and PAT would differ in clinical practice (and the necessary additional margins which may result from this) is therefore currently unclear.…”
Section: Relative Impact Of Proton Arc Therapymentioning
confidence: 99%
“…It has, however, been shown that, while PAT delivery times exceed IMPT treatment times when energy layer switching times are higher, delivery times of proton arc therapy treatments can become equivalent to or even lower than their IMPT counterparts if energy layer switching is sufficiently fast (Ding et al 2016, Liu et al 2020b, 2023a). An increase in the delivery tolerance window up to ±1.25°has been to be capable of considerably reducing PAT delivery times as well (Liu et al 2023b). The extent to which delivery times of IMPT and PAT would differ in clinical practice (and the necessary additional margins which may result from this) is therefore currently unclear.…”
Section: Relative Impact Of Proton Arc Therapymentioning
confidence: 99%
“…The idea is that this window should be small enough that it does not matter at which exact angle a spot is delivered, as long as it is within the specified window. The dose perturbation should be small enough to be negligible (Liu et al 2023). See figure 1 for an illustration of this concept.…”
Section: Proton Arc Preliminariesmentioning
confidence: 99%